Background Characteristics of the Individuals Attaining Higher Education in India: A Sociological Study of Srinagar City - Bazaz, Rabiya Yaseen; Akram, Mohammad (Journal of Education Culture and Society, 2020)
Aim: Higher education has experienced major changes in last few decades in India in terms of its expansion, content and reach. Massification of higher education has increased access to education and people belonging to different social backgrounds are getting enrolled in higher education. A pertinent question that emerges here is: what kind of relationship exists between the background characteristics of people and the levels and types of higher education they attain? This descriptive study provides a comprehensive answer.Method: This empirical work is conducted in Srinagar city of India. It covered 704 respondents belonging to 245 households. Survey method was used for collecting primary data and structured interviews were conducted by making use of interview-schedule.Results: This study finds that higher education in Srinagar is readily available for many but such availability is embedded within constraints related to gender, age, occupation and education of parents and caste related identities. People coming from different social backgrounds acquire different types and levels of higher education. It creates hierarchy among and within academic courses of higher education and inequalities among the groups.Conclusion: Higher education reflects as well as promotes social inequalities in contemporary context and thus the egalitarian goals of higher education are getting compromised. There is need to bring change in the courses and contents of higher education so that it can address to dynamic needs of people coming from different backgrounds. Education needs to become a vehicle for liberation and social transformation and should not remain a mere agency of social reproduction.Key words: social background; courses within higher education; higher education in different contexts; gender; caste; parent’s background; descriptive study.